1994
DOI: 10.1007/bf00211013
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and parental origin of hypermethylated RB1 alleles in retinoblastoma

Abstract: The retinoblastoma susceptibility (RB1) gene contains an unmethylated CpG-rich island at its 5' end. Using methylation-sensitive restriction enzymes, we have investigated the methylation status of this island in 21 sporadic unilateral retinoblastomas and 30 hereditary retinoblastomas. Three sporadic unilateral tumors were found to have hypermethylated RB1 alleles. In two tumors, the paternal allele was methylated, whereas the maternal allele had been lost. Cultured cells from one of these tumors were studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
95
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 15 publications
4
95
0
3
Order By: Relevance
“…DNA methylation that results in gene silencing during tumorigenesis has been observed in numerous genes, including Ecadherin, RB, p16, p15, MLH1, and PTEN [17][18][19][20]. In this study, we demonstrated that methylation of the ER gene occurred in nearly half of the breast cancer cases and is highly correlated with ER-negativity (P < 0.00001) and BRCA1 methylation (odds ratio 3.12, 95% confidence interval 1.10-9.68, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation that results in gene silencing during tumorigenesis has been observed in numerous genes, including Ecadherin, RB, p16, p15, MLH1, and PTEN [17][18][19][20]. In this study, we demonstrated that methylation of the ER gene occurred in nearly half of the breast cancer cases and is highly correlated with ER-negativity (P < 0.00001) and BRCA1 methylation (odds ratio 3.12, 95% confidence interval 1.10-9.68, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…It contains CpG islands that are frequent sites of methylation (Ohtani-Fujita et al, 1993;Stirzaker et al, 1997). Hypermethylation in the RB1 promoter region has been reported in 13% of unilateral retinoblastomas (Greger et al, 1994;Sakai et al, 1991) and 27% of pituitary adenomas (Simpson et al, 2000), suggesting that promoter hypermethylation is an alternative mechanism for mutational loss of RB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation has been considered one of the mechanisms of inactivation of the RB1 gene in the two-hit theory, because the majority of retinoblastomas with promoter hypermethylation showed LOH on the RB1 locus (Greger et al, 1994;Sakai et al, 1991). However, there is recent evidence that hypermethylation without LOH at this locus may be sufficient to cause loss of RB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of TSG inactivation by de novo methylation varies between TSGs and between cancers. Initially, epigenetic silencing of TSGs was reported as an alternative, but a minor mechanism of inactivation for TSGs such as RB1 and VHL (Greger et al, 1994;Herman et al, 1994). However, recently a new class of TSGs has been recognised for which epigenetic silencing is the overwhelming mechanism of inactivation and somatic mutations are rare.…”
mentioning
confidence: 99%